Genetic and nutritional factors contributing to hyperhomocysteinemia in young adults - SCOTT, JOHN MARTIN (American Society of Hematology, 2003)
A modestly elevated total plasma homocysteine concentration (tHcy) is generally accepted as an independent and graded risk factor for various pathologies, including vascular diseases, neural tube defects, Alzheimer disease, and pregnancy complications. We analyzed 5 common functional polymorphisms in enzymes involved in homocysteine metabolism (ie, methylenetetrahydrofolate reductase [MTHFR] 677C>T and 1298A>C, methionine synthase [MTR] 2756A>G, cystathionine -synthase [CBS] 844ins68, and methionine synthase reductase [MTRR] 66A>G) in 452 young adults, and quantified their independent and interactive effects on tHcy concentrations. Serum folate, red cell folate, vitamin B12, and tHcy concentrations were significantly influenced by MTHFR 677C>T genotypes. A particularly strong interaction was observed between the MTHFR 677TT genotype and serum folate, which led to a high tHcy phenotype that was more pronounced in males. The genetic contribution to the variance in tHcy was estimated to be approximately 9%, compared with approximately 35% that could be attributed to low folate and vitamin B12. Our study indicates that dietary factors are centrally important in the control of tHcy levels in young adults with additional, but somewhat weaker, genetic effects. These data underscore the potential benefits that may be gained by improving the dietary status of young adults, and provide support for the implementation of folate/B-vitamin food fortification programs.
PUBLISHED
Keywords: Biochemistry